Internal mammary lymph nodes identification from isolated sternum of human cadaver - Pinheiro,Luiz Gonzaga Porto (2006)
PURPOSE: To identify the lymph nodes positioned along the internal mammary vessels in isolated sternum of human cadaver and to standardize the surgical approach to those nodes, in order to establish anatomical landmarks to be used with the current techniques of mammary gland sentinel lymph node detection. METHODS: Ten sternum plates removed from unclaimed cadavers were used in this study. Sternal plates were removed using bilateral incisions of the ribs at the midclavicular lines. The characterization of the internal mammary vessels and the anatomical integrity of the parietal pleura were indispensable requirements during the procedure. RESULTS: A total of 29 lymph nodes were removed from the 2nd (13) and the 3rd (16) intercostals spaces. Almost 50% of all nodes collected were located medially to the vessels. CONCLUSION: The approach used is a reliable surgical technique for removing lymph node from sternal plates. The model is therefore valuable for breast surgeons training in sentinel node biopsy, an important procedure for breast cancer patients.